Anti-Interleukin-16-Neutralizing Antibody Attenuates Cardiac Inflammation and Protects against Cardiac Injury in Doxorubicin-Treated Mice - Jianwei Zhang; Zicong Yang; Zhishan Liang; Mengjie Wang; Changxing Hu; Chao Chang; Lei Shi; Qingwei Ji; Ling Liu (Mediators of Inflammation)
Background. Interleukin-16 (IL-16) is an important inflammatory regulator and has been shown to have a powerful effect on the regulation of the inflammatory response. Cardiac inflammation has been reported to be closely related to doxorubicin- (DOX-) induced cardiac injury. In this study, the role of IL-16 in DOX-induced cardiac injury and the possible mechanisms were examined. Methods. Cardiac IL-16 levels were first measured in DOX- or saline-treated mice. Additionally, mice were pretreated with the anti-IL-16-neutralizing antibody (nAb) or isotype IgG for 1 day and further administered DOX or saline for 5 days. Then, cardiac injury, cardiac M1 macrophage levels, and cardiomyocyte apoptosis were analyzed. The effects of the anti-IL-16 nAb on macrophage differentiation and cardiomyocyte apoptosis were also investigated in vitro. Results. DOX administration increased IL-16 expression in cardiac macrophages compared with that of saline treatment. The anti-IL-16 nAb significantly decreased serum levels of lactate dehydrogenase (LDH), myocardial-bound creatine kinase (CK-MB), and cardiac troponin T (cTnT) and elevated cardiac function in DOX-induced mice. Treatment with the anti-IL-16 nAb also reduced p65 pathway activation, decreased M1 macrophage-related marker and cytokine expression, and protected against cardiomyocyte apoptosis in DOX-induced mice. In cell studies, the anti-IL-16 nAb also reduced DOX-induced M1 macrophage differentiation and alleviated apoptosis in cardiomyocytes cocultured with macrophages. Conclusions. The anti-IL-16 nAb protects against DOX-induced cardiac injury by reducing cardiac inflammation, and IL-16 may be a promising target to prevent DOX-related cardiac injury.